Simulation of the soil washing-out and cavitation outside the concrete casing in the process of spillway operation - Skipochka, S.I.; Krukovskaya, V.V.; Grebenyuk, S.D. (Геотехнічна механіка, 2014)
Chemical and mechanical processes of the buried concrete elements breakage, water filtration through the damaged concrete into enclosing soil, and cave formation due to the soil washing-out were studied with the help of computer simulation. The authors created several mathematical models which describe: moisture diffusive transfer in the porous structure of concrete with taking into account water participation in the chemical reactions; changes in the stress state of the buried concrete constructions and strength retrogression caused by high humidity and corrosive medium; and water filtration through the damaged concrete into enclosing soil. The models adequacy was verified by a set of full-scale experiments. The data obtained by the calculations were successfully applied during reconstruction of hydraulic objects in the mine Colliery Group «Pokrovskoye».